Flood Mitigation Priority Strategy to Reduce Community Vulnerability in the Downstream Area of the Setail Watershed, Banyuwangi - Gigik Nurbaskoro; Indarto Indarto; Elida Novita; Mohamad Wawan Sujarwo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Floods that repeatedly occur in the downstream area of the Setail Watershed have caused significant damage to infrastructure, community livelihoods, and social systems in the region. This condition demands the implementation of effective and sustainable mitigation strategies to reduce flood risks and impacts. This study aims to determine priority flood mitigation strategies to reduce community vulnerability in the downstream area of the Setail Watershed. The identification of mitigation criteria was first conducted through interviews with flood-affected communities to capture relevant local factors. These criteria were then discussed with disaster mitigation experts and stakeholders, and the results of the questionnaires were analyzed using the Analytical Hierarchy Process (AHP) method to evaluate and rank the mitigation strategies. The results show that the three main priority strategies are flood risk mapping with a score of 0.22, community education and awareness with a score of 0.18, and zoning and spatial planning with a score of 0.15. These strategies are expected to serve as the basis for the preparation of local government action plans to minimize future flood impacts and enhance community resilience and well-being.